Carnavalização no futebol: “espaços e tempos de liberação social nas manifestações das torcidas manauenses de futebol” - (:unkn) unknown (Universidade Federal do Amazonas, 2018)
This research had as its theme the Carnavalization in Football, spaces and times of social liberation in the manifestations of the soccer fans of Manaus. We chose as general objective and guiding the development of this thesis, to demonstrate the existence of carnavalized forms of liberation expressed in the cultural manifestations of the soccer fan. In methodological terms this study is anchored in the perspective of phenomenology. For these reasons, our research was characterized as a study of the ethnographic type with a qualitative approach and had an interdisciplinary character, since it covered several areas of knowledge such as Anthropology, Sociology, Physical Education and Sports. As a data collection instrument, a forms was used and 234 fans of professional football teams and 187 fans of amateur teams were part of our survey. In addition to the use of forms, in our study we also used the field diary. As a locus of our research we chose the great stadium that hosted the 2014 World Cup in Manaus the Arena of the Amazon, and the other two stadium stages of the games of the Amazonian football championship 2018 and newly opened stadium Carlos Zamith. In addition to these places, our research also favored the spaces of Praca do Caranguejo in the Eldorado Complex, located in the central-western zone of Manaus, consolidated as a place of great crowd of fans. The results of our research have demonstrated that carnivalization is widespread or partial, as it is present in the fanning practices, characterized mainly by the tendency to relax the formalities and tensions that dominate the daily social relationship, exerting a significant psychosocial function in their lives. We also found that carnivalization of the manauense fans presents mimetic, cathartic elements and the social relations between the agents who watch football matches, in bars or at stadiums, acquire a specificity based on the "liberalization" inherent to the carnival period.
Keywords: Futebol; Torcedores; Carnavalização; CIÊNCIAS SOCIAIS APLICADAS